FILSAFAT KURIKULUM DAN PENGAJARAN - Seknun, Yusuf (Universitas Islam Negeri Alauddin Makassar, 2017)
First of all, on the background of philosophy required an ontological basis of the science of education. The aspect of reality that reaches the theory and science of education through the experience of the senses is the world of human experience empirically. Object material science education is a complete human, complete human aspects of his personality, namely humans who have noble character in the educational situation or expected beyond human beings as social beings remember as a citizen he has the characteristics of good citizens (good citizenship or the best citizenship). The epistemological basis is required by education or science education experts to develop their knowledge productively and responsibly. Although data collection in the field can be partially performed by novice personnel but the study of the formal object of the science of education reveals a phenomenological approach that will establish an empirical study with a qualitative-phenomenological study. The phenomenological approach is qualitative, meaning it involves the personal and self-researcher as a data collection instrument in post-positivism. Therefore, the study and data collection is directed by educators or scientists as experts who are honest and united with the object.